A Theory of Contemporary Rhetoric. - Andrews, Richard (Taylor and Francis, 2013)
A Theory of Contemporary Rhetoric describes, explains, and argues the overarching theory of contemporary rhetoric. This current view of rhetoric brings together themes in the communication arts, including political literary criticism; bi- and multi-lingualism; multimodality; framing as an artistic and sociological device for composition and interpretation; literacy in the digital age; and the division between fiction and 'non-fiction' in language/literature studies. Chapters explore the implications of rhetoric for particular aspects of the field. Discussions throughout the book pr.